Synthesis and Characterization of Dealuminated Ultra-Stable Zeolite Y Supported Cesium Salt of Phosphotungstic Acid for the Esterification of Acrylic Acid with Butanol - Chin, S. Y.; M. R., Kamaruzaman; M. A. A., Ahmad (Taylor & Francis, 2016)
Wastewater containing 10–20 wt% of acrylic acid (AA) is released from petrochemical industries during the manufacture of AA, acrylic ester, water-soluble resin and flocculants. This untreated wastewater could have detrimental effects on the environment due to its high chemical oxygen demand. Heterogeneously catalyzed esterification of this wastewater with alcohol in a reactive distillation column (RDC) could be a promising treatment method to recover AA from the wastewater. Considering the importance of a water-resistant catalyst in this method, this work has synthesized and tested a potential catalyst, cesium salt of phosphotungstic acid (CsxH3-xPW) supported on dealuminated ultra-stable zeolite Y (DUSY), for the esterification of AA with 1-butanol (BuOH). The catalysts were synthesized through impregnation using various solvents, DUSY with different compositions of silicon (Si) to aluminium (Al), compositions of cesium (Cs) and precursor loadings. The 30%(Cs1.5(IWI)H1.5PWIWI)DEE/DUSY60 was the best catalyst, giving reasonably high yield and low leaching. The BA yield obtained was 9.53% at 80°C, stirring speed of 500 rpm, catalyst loading of 10 wt% and MAA:BuOH of 1:3 for 4 h.